1994
DOI: 10.1080/09553009414550951
|View full text |Cite
|
Sign up to set email alerts
|

Cell Cycle Delays Induced by Heavy Ion Irradiation of Synchronous Mammalian Cells

Abstract: Cell cycle delays in V79 Chinese hamster cells induced by heavy ion exposure have been investigated using flow cytometry. Synchronous cell populations in G1, S and late-S G2/M phase were used, which were prepared by centrifugal elutriation. Cells were irradiated with particles from Z = 10 (neon) up to 96 (uranium) in the energy range from 2.4 to 17.4 MeV/u and the LET range from 415 to 16,225 keV/micron at the UNILAC at GSI, Darmstadt. For comparison, experiments with 250 kV X-rays were performed. For light pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 60 publications
(22 citation statements)
references
References 27 publications
2
17
0
1
Order By: Relevance
“…Particle exposure induces pronounced cell cycle delays (e.g. Scholz et al 1994, Ritter et al 1996, and these delays are related to the aberration burden of cells. For normal human fibroblasts, which respond to DNA damage not only with a transient, but also with a long-term cell cycle arrest (figure 2 and 3) (see Sections 4.1.1 and 4.1.2), the relationship between cell cycle effects and the expression of aberrations in metaphase cells might be even more complex.…”
Section: Analysis Of Radiation-induced Aberrations In Metaphase Cellsmentioning
confidence: 99%
“…Particle exposure induces pronounced cell cycle delays (e.g. Scholz et al 1994, Ritter et al 1996, and these delays are related to the aberration burden of cells. For normal human fibroblasts, which respond to DNA damage not only with a transient, but also with a long-term cell cycle arrest (figure 2 and 3) (see Sections 4.1.1 and 4.1.2), the relationship between cell cycle effects and the expression of aberrations in metaphase cells might be even more complex.…”
Section: Analysis Of Radiation-induced Aberrations In Metaphase Cellsmentioning
confidence: 99%
“…Yet, evidence is growing that this assay is not reliable in the case of high LET radiation. The exposure of cells to high linear energy transfer (LET) radiation delays cell cycle progression more than exposure to low LET radiation (e.g., Collyn-D'Hooghe et al 1981, Lü cke-Huhle et al 1982, Scholz et al 1994) and it has been recently shown that the delay is related to the number of aberrations harboured by a cell. For example, in human lymphocyte populations exposed to particles with an LET exceeding 100 keV mm 71 , a signficant increase in the aberration yield with sampling time was observed.…”
Section: Introductionmentioning
confidence: 99%
“…Zellzyklusbedingte Unterschiede in der Radiosensitivität von Zellen sind gering, so dass sich Unterschiede in der Therapieantwort langsam und schnell proliferierender Tumoren reduzieren sollten. Es wurden zudem eine Verzögerung der Zellteilung nach Hoch-LET-Bestrahlung sowie eine Abnahme der Schutzeffekte durch die benachbarten Zellen beschrieben [2,17].…”
unclassified